Tertiary-level students' L2 reticence in relation to teacher leadership in an English-medium classroom. (June 2022) - Kang, Dae-Min; Zhu, Jianbin
Abstract: The present study investigated the relationships between second language (L2) reticence and language teacher leadership. Twenty graduate students enrolled in an English-medium course at a Chinese university and their teacher participated in this case study. The research instruments included classroom observations, reflective journal writing, and in-depth, semi-structured interviews. The results showed that the students' L2 reticence persisted throughout the observation period in complicated interaction with the teacher's leadership. Both the students and teacher were found to have exercised their agency in relation to L2 reticence and teacher leadership. Based on the findings of the study, implications are suggested.